1995
DOI: 10.1099/0022-1317-76-4-1025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methyltransferase inhibitors on the regulation of baculovirus protein synthesis

Abstract: In the presence of the methyltransferase inhibitor 3-deazaadenosine (3DA-Ado) the production of infectious Autographa californica nuclear polyhedrosis virus (AcMNPV) in tissue culture was only slightly affected, while the synthesis of very late proteins (polyhedrin and pl0) was abolished. The synthesis of the influenza virus proteins NS1 and HA, expressed under the polyhedrin promoter, was also abolished by 3DA-Ado. Furthermore, 3DA-Ado interfered with the shut-off of early and late AcMNPV proteins. Most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…SARS NendoU specifically recognizes uridylate bases at GUU sites of RNA (Ivanov et al, 2004). The virus protects its own RNA by methylating its 5 0 termini CAP by using an Ado-Met-dependent RNA methyltransferase (von Grotthuss et al, 2003), a process that is imperative during coronaviral replication and an active area of therapeutic intervention (Bach et al, 1995;Vlot et al, 2002). The possibility that SARS ADRP, NendoU, and the methyltransferase might be acting in concert and might therefore be functionally linked has been the subject of previous speculation .…”
Section: Discussionmentioning
confidence: 99%
“…SARS NendoU specifically recognizes uridylate bases at GUU sites of RNA (Ivanov et al, 2004). The virus protects its own RNA by methylating its 5 0 termini CAP by using an Ado-Met-dependent RNA methyltransferase (von Grotthuss et al, 2003), a process that is imperative during coronaviral replication and an active area of therapeutic intervention (Bach et al, 1995;Vlot et al, 2002). The possibility that SARS ADRP, NendoU, and the methyltransferase might be acting in concert and might therefore be functionally linked has been the subject of previous speculation .…”
Section: Discussionmentioning
confidence: 99%
“…In 1995, it was first reported that in the presence of DAC, the production of infectious Autographa californica nuclear polyhedrosis virus (AcMNPV) was only slightly affected, while the synthesis of late proteins (polyhedrin and pl0) was abolished, similar to the methyltransferase inhibitor 3-deazaadenosine (3DA-Ado) [ 43 ]. It has also been reported that when applied a few hours prior to virus inoculation, DNA methyltransferase inhibitors (AZA, azacytidine and DAC, decitabine) improved baculovirus-mediated gene expression by fourfold or more in all four mammalian cell lines (CHO, CNE, HEK293, and HepG2 cells) [ 44 ].…”
Section: Antiviral Effects Of Decitabinementioning
confidence: 99%